Examining the Role of Digital Marketing in Shaping Consumer Communication and Behavior - Bharti, Rakshak; Khatri, Urvija; Duralia, Oana Alexandrina (Feedback International Journal of Communication, 2024)
This study investigates the transformative impact of digital marketing on consumer communication and behavior, with a focus on tools such as mobile applications, social networks, and electronic word-of-mouth (eWOM). As digital platforms reshape consumer interaction, understanding their collective influence has become critical for businesses aiming to improve engagement and competitiveness, especially within the tourism industry. The integration of personalized, data-driven communication frameworks provides businesses and consumers with unparalleled access to interaction and feedback mechanisms. A mixed-methods approach was employed, incorporating a systematic review of academic literature and primary data collection. The review analyzed peer-reviewed articles published within the past decade to ensure relevance to contemporary digital marketing practices. Semi-structured interviews were conducted with industry professionals in tourism marketing, providing insights into the practical application of digital tools. Additionally, an online survey gathered quantitative data from active consumers on digital platforms, focusing on their preferences and behaviors. Mobile applications emerged as critical for streamlining processes such as booking and feedback collection, with 89% of surveyed users citing increased convenience. Social networks facilitated peer influence and trust-building, with 75% of decisions being shaped by user-generated reviews. eWOM highlighted authenticity as a driver, positively influencing 85% of consumer trust while negatively affecting 62% when feedback was poor. Companies utilizing digital marketing tools recorded a 27% higher customer retention rate than those relying on traditional methods.